Study of Student Community Movements Against the Development of a Geothermal Power Plant in Gunung Talang - Dian Kurnia Anggreta; Gumilar Rusliwa Somantri; Semiarto Aji Purwanto (The Journal of Society and Media, 2022)
This research aims to analyze the student community's resistance to developing geothermal power plants (in Indonesia, referred to as Pembangkit Listrik Tenaga Panas Bumi, abbreviated as PLTP), analyze movement patterns, and assess the resistance movement's challenges. This study used qualitative research methods. Data were collected by interview, observation, and document study. According to the study's findings, the rejection movement began with local media coverage of police officers' coercive tactics to secure the activities of corporations conducting preliminary research at the project site. The student community perceives PLTP development activities as environmental injustice, even though the projects are ostensibly environmentally friendly. Patterns of rejection movements are carried out in three ways: 1) Disseminating information; 2) Employing provocative tactics (delivering criticism of environmental injustice and police repression through performing arts such as theatre, murals, short monologues, and poetry readings); and 3) Mobilizing public support (through campaigns in public spaces and using social media, to campaign for the potential impact of PLTP development). The roots of rejection are typically minimal because there is no apparent conflict of interest between students and the PLTP development business (in contrast to the local community as the affected party).